Evaluation Of Drill Bit Selection On Basement Layer Exploration Drilling In AFM Block - Afi Maulana; Aris Buntoro; Dedy Kristanto (Journal of Petroleum and Geothermal Technology, 2023)
In one of the exploration drilling of the AF-01 well, there was a drilling problem on the 8 in hole when it penetrated the basement layer. ROP at the time of drilling the basement layer is far below the estimated ROP.By setting MSE as, ROP is increased so that cost savings are obtained from reducing rig time. A qualitative analysis of drillbit selection was carried out based on the type and design of the drillbit as well as the characteristics of the basement rock to be penetrated.In addition to the qualitative and quantitative assessment was carried out through the calculation of the PDC Design Index, MSE, DSE and CPF on each drill bit.ROP of Hybrid PDC-1 increased 500% when compared to PDC-1. The MSE and DSE produced by the Hybrid PDC-1 are 750% smaller than the PDC-1. Using the Hybrid PDC-1, drilling costs can be reduced up to USD 2,105,481.The low ROP at the time of drilling the basement layer in well AF-01 was due to the incompatibility of the PDC-1 bit used for the type of rock being penetrated. Hybrid PDC-1 is the most optimum bit to penetrate the basement layer in the AFM Block.